Towards policy-relevant science and scientifically informed policy: Political economy of the use of knowledge and research evidence in urban resilience interventions in the Philippines - Pellini, Arnaldo (Animo Repository, 2013)
The United Nations 2009 Global Report on Disaster Risk Reduction ranked the Philippines as the third most disaster-prone country in the world, and the country with the largest population exposed and displaced every year due to natural disasters. When natural disasters such as violent floods, typhoons or earthquakes occur, the damage has long lasting effects, not only on the economy but more importantly, on people’s lives and a community’s sense of security and normalcy. While natural disasters cannot be avoided, it is the duty of governments and civil society in general to develop initiatives that reduce the negative effects natural disasters have on people’s lives. In this study we look at urban resilience polices – the tools governments use to make decisions and implement disaster risk reduction, as well as initiatives aimed at reducing the negative effects of natural disasters. We define urban resilience as ‘the ability of an urban system, community or society exposed to hazards to resist, absorb, accommodate and recover from the effects of a hazard in a timely and efficient manner, including through the preservation and restoration of its essential basic structures and functions.’ (UNISDR 2009). As noted by Ashley (2011)1, ‘we know how good decision-making works. It should be fact- based, deliberative and tested by real arguments. This means it needs people who have the knowledge to engage and the self-confidence to challenge assumptions.’ To paraphrase Ashley, we could say that ‘we know how good policy works. It should be fact-based, deliberative and tested by real arguments.’ This study examines whether the processes that govern policy and decision-making on resilience to natural disasters in urban areas of the Philippines are good, i.e. fact-based and deliberative, and tested by real arguments. Seven illustrative Local Government Units (LGUs), (Tabaco City, Baguio City, Marikina City in Luzon, Iloilo City and Cebu City in Central Visayas and Davao City and Cagayan de Oro City in Mindanao) were selected as case studies to better understand the factors that favour or hinder the use of knowledge and research evidence in the design and implementation of urban resilience policies and practice. The choice of the case study areas is linked to the occurrence of natural disasters, and the experience of decision-making and local planning on climate change/urban resilience. The research was conducted by adopting a political economy analysis to create an analytical framework that focuses on the specific topic of use of knowledge in policy decision-making process. Data collection was conducted through focus group discussions and semi structured interviews. The key finding of our study is that the Republic Act 10121, which was passed in 2010,established, among other things, a legislative framework that enables greater use of scientific evidence in designing disaster risk reduction policies and interventions, both at national and sub-national level. It is still early days to assess the impact of the new legislation, and there are delays in the implementation of the Republic Act, such as training line agency staff at sub-national level on preparing against disasters and developing resilient communities, as well as responding to natural disasters. Another important finding is that LGUs do not usually demand or procure research and analysis to inform their policy decision-making process on disaster risk reduction. The demand for use of scientific knowledge by policy-makers is linked to the occurrence of a natural disaster rather than the risk of occurrence of a natural disaster. A topic that is politically loaded is the issue of relocating communities living in areas at high risk of natural disasters. As well as the economic costs, a decision to relocate communities is almost certain to encounter strong opposition and protests, which can be very ‘expensive’ politically, and end in action being delayed. Therefore, while relocation can be considered an evidence-based and technically sound solution, it is often not politically feasible. We found exceptions to the limited use of evidence in policy decision-making in this area, with examples of greater engagement between local administrations and academic institutions. These cases are context specific. In the province of Albay (a high-risk area) the governor was able to build political will on disaster prevention and establish close links with the Climate Change Academy at Bicol University. In Cagayan de Oro, following Typhoon Sendong in 2011, Xavier University collaborated with the local administration. In Davao, the Davao Association of Colleges and Universities has an explicit objective to increase the use of research evidence in policy-making. These examples show it is possible to develop in the Philippines evidence-based decision-making processes on disaster risk reduction that can contribute to building more resilient urban communities.